Coexistence of adenomyosis in women operated for benign gynecological diseases - Ozkan, Zehra Sema; Kumbak, Banu; Cilgin, Hasan; Simsek, Mehmet; Turk, Bilge Aydin (Informa Healthcare, 2012)
Background: To compare demographic, clinical and histopathological characteristics of women diagnosed with adenomyosis (AG) after hysterectomy to those of women diagnosed with leiomyoma (LG) and to investigate the predisposing factors for AG. Methods: This study was carried out on 204 patients who underwent gynecologic surgery for various indications except for gynecologic malignancy between January 2005 and December 2009 and whose histopathological analysis of hysterectomy/myomectomy specimen revealed either AG or LG. Women with AG and those with LG were compared with respect to age, parity, menstrual pattern, history of induced abortion, history of prior uterine surgery, smoking, dysmenorrhea, dyspareunia, chronic pelvic pain and coexisting endometrial and ovarian pathologies. Results: The mean age of our patients was 51 +/- 8 years (range 28-85), 40% of them were postmenopausal, and 64% had a history of uterine surgery. The mean age (p=0.014), gravida (p=0.018), parity (p=0.017) and previous endometrial sampling (p<0.01) were significantly higher in AG. Main symptoms were abnormal uterine bleeding (39%), dysmenorrhea (63%) and nonmenstrual pelvic pain (62%). Age (p=0.01), menometrorrhagia (p=0.02) and endometrial sampling (p<0.01) were the significant covariants in binary logistic regression for AG. Conclusion: AG is an enigmatic disease frequently causing gynecologic complaints and endomyometrial junction deterioration during endometrial sampling may be a trigger point for developing AG.
Keywords: adenomyosis; endomyometrial junction; hysterectomy; leiomyoma; pelvic pain